Pengaruh Kepemimpinan terhadap Kinerja Perawat di Ruang Perawatan Kelas III RS Husada Jakarta - Mose, Ria Efkelin (Jurnal Kesehatan Holistic, 2020)
Good leadership in the hospital will improve nurse performance. Performance of nurses can improve services quality to patients This study was conducted to determine the influence of leadership on the performance of nurses at Husada hospital with a total sample of 47 nurses working in Melati Room. The analysis used include validity, reliability test, classical assumption test, correlation and regression testing either partially or simultaneously with the processing of the statistical analysis. Results of the analysis showed that simple leadership is considered an important contribution and a significant effect in improving the performance of nurses in the amount of 91.3%, while the remaining 8.7% is explained by other variables not examined. The right leadership for health service institutions is expected to be able to improve the performance of nurses so that health services can be provided optimally.